Communication for health promotion: the advertising campaigns on tuberculosis in Brazil - Maira Rossetto; Lilian Zielke Hesler; Rosana Maffacciolli; Cristianne Famer Rocha; Dora Lucia de Oliveira (Universidade Federal de Santa Maria, 2017)
Aim: to analyze the content of advertising campaigns on tuberculosis produced by the Brazilian Ministry of Health in Brazil. Method: supported by the Health Promotion and Health Education benchmarks, analysis have been conducted in the campaigns carried out in the years of 2007, 2008, 2010 and 2011. Results: two thematic categories resulted from the analysis: "Cough can be tuberculosis! The treatment is free and should not be interrupted!" and "The ill and the disease: an image composition in advertising campaigns." The texts appeal for individual consciousness and self-care based on the connection among health, absence of symptoms and adopting a surveillance attitude to avoid them. The used images are constituted by elements with low representativity of the diseased person's reality. Conclusions: these reflections contribute to the field of health and nursing, especially as they produce an ethical conscience committed to reducing vulnerabilities and protecting life